Isolated and combined effects of steam inhalation via the voiced high-frequency oscillation technique after a short vocal loading task in healthy female voices. - Peru Keskin, Beyza Sena; Yılmaz, Göksu; Saraç, Ayşe Buse; Elgörmüş, Mehmet Nuri; Kaya, Tuğba; Konrot, Ahmet (Logopedics Phoniatrics Vocology, 2025)
Objective: The first aim of the study, to determine the effects of a vocal loading task (VLT) involving reading a passage at a level of 80–85 dBA(30 cm) for 10 minute (min) on voice. The second aim is to identify the effects of three different therapeutic strategies performed immediately after the VLT on voice. Method: The sample of the study included 32 normophonic female participants. The research procedure involved three different therapeutic strategies: sterile water nebulization, voiced oral high-frequency oscillation (VOHFO) and the combined application following three different vocal loading tasks performed for 10 min. The assessments were made using acoustic, electroglottographic, perceived vocal effort (Borg CR-10) measurement methods. Results: The 10 min VLT did not significantly affect the acoustic (except for fundamental frequency-Fo) or electroglottographic parameters of the habitual voice, while it led to an increased level of perceived vocal effort scores and Fo values. Perturbation and perceptual effort decreased after all three therapeutic interventions, but Fo remained higher than baseline; EGG-contact quotient (CQ) decreased after VOHFO-inclusive therapeutic interventions and perceptual effort level did not decrease after nebulization but decreased after VOHFO-inclusive interventions. Conclusion: The 10 min VLT, which was of a short duration, led to an increased level of perceived vocal effort scores and Fo values. In addition, all therapeutic interventions were found to decrease perturbation and perceived vocal effort. However, according to the EGG-CQ data, the addition of therapeutic factors such as VOHFO to superficial vocal fold hydration procedures may further enhance their beneficial effects on the voice.